Answer: d
Step-by-step explanation: you just divie them and mutip hehe
sorrt i hope this help =)
when y = -11, 0 + y is equal to -11.
the question is asking us to add 0 to the given value of y. the given value of y is -11, so place -11 into 0 + y and you get 0 + -11. since you are adding zero, you are making no changes to the y value, so it stays at -11.
<em>hope this helps and have a great day!</em>
Answer:
This is not a real question rephrase
Step-by-step explanation:
Answer:
50/50
Step-by-step explanation:
Answer:
65 parts
Step-by-step explanation:
20*3=60
20*(15/60)= 5
60+5=65